Comparison of Resin Infiltration Technique with Conventional Preventive Applications on Occlusal Fissures: EDS and SEM Analyses - Sidika Aynur Horuztepe; Esra Ergin; Alev Onen; Sevil Gürgan (University of Zagreb. School of Dental Medicine, 2020)
Objective: To compare the subsurface mineral loss preventing capability of resin infiltration technique with topical fluoride and fissure sealant applications to demineralized occlusal fissures under simulated oral conditions. Materials and Methods: Occlusal surfaces of 64 extracted intact human third molars were demineralized. Next, the teeth were classified into four groups according to preventive applications (n = 16): G1, Specimens used as the control group with no preventive treatment; G2, Topical fluoride application (APF Gel/ DEEPAK); G3, Fissure sealant application (ClinproT-MSealant/ 3M ESPE); and G4, Resin infiltration technique (Icon/ DMG). Chemical compositions before pH cycling were evaluated for eight specimens from each group. The remaining eight teeth from each group were subjected to pH cycling for 15 days to simulate the oral conditions. Subsequently, the specimens were fractured after immersion in liquid nitrogen and the subsurface fluoride (F), calcium (Ca), phosphorus (P) levels, and Ca/P ratio of each specimen were measured using energy dispersive x-ray spectrometer (EDS). The data were subjected to statistical analysis (p = 0.05). The effects of preventive applications to surface topography of specimens were evaluated using scanning electron microscope (SEM). Results: There were no significant differences among the groups in subsurface F, Ca, and P levels and Ca/P ratios before or after pH cycling (p > 0.05). All three preventive applications were effective during pH cycling according to SEM observations. Conclusions: The subsurface mineral loss preventing capability of resin infiltration technique applied to occlusal fissures was comparable to topical fluoride and fissure sealant applications. Clinical significance: The resin infiltration technique could represent a valid alternative to traditionally used both preventive and restorative treatments for treating initial carious lesions on occlusal fissures, offering the advantages of better resin penetration and retention.